Quantification of cell-free DNA from bladder cancer patients after long-term storage and its use in determining CCAT2, HRAS, and RET polymorphism: A pilot study (Annals of Medical Research, 2021)
Aim: The level of free DNA is used as a cancer biomarker due to having several advantages related to lower cost, easy applicability, and rapid results compared to invasive methods.Materials and Methods: This study investigated whether or not free DNA functions as intended when stored. The free DNA isolated for this purpose was kept at –80 degrees for four years. Then, the level of free DNA was measured in patients with bladder cancer by both photometric and fluorometric methods, and it was investigated whether this biomarker was effective in determining Single Nucleotide Polymorphisms (SNP). The gene names and the reference numbers of the locations where polymorphism was expected were as follows: CCAT2 (rs6983267), HRAS (rs12628), and RET (rs1799939).Results: According to the results, having the T allele at rs12628 increases the risk of disease by 2.6 times (OR: 2.60; 95% CI: 1.10–6.10) and having the G allele at rs1799939 increases the risk of disease 2.7 times (OR: 2.70; 95% CI: 1.12–6.69).Conclusions: The general findings showed that fluorometric measurements were more advantageous when considering the sensitivityof free DNA measurements. It was also concluded that, if treated rapidly and conserved in appropriate laboratory conditions, free DNA can be effectively used in SNP studies. This study provides important data to demonstrate the quality of free DNA.